Immune‐related adverse events in urothelial cancer patients: Adjustment for immortal time bias. Issue 11 (2nd September 2022) - Otsuka, Hikari; Kita, Yuki; Ito, Katsuhiro; Sano, Takeshi; Inokuchi, Junichi; Tomida, Ryotaro; Takahashi, Atsushi; Matsumoto, Kazumasa; Kurahashi, Ryoma; Ozaki, Yu; Uegaki, Masayuki; Maruyama, Satoru; et al.
Abstract: To investigate the association between the onset, severity, and type of immune‐related adverse events (irAEs) and the efficacy of pembrolizumab in patients with platinum‐pretreated advanced urothelial carcinoma (UC), we retrospectively collected clinical datasets of 755 patients and conducted landmark analysis. Patients who survived for fewer than 3 months were excluded from the evaluation to reduce the immortal time bias. In total, 620 patients were evaluated, of whom 220 patients (35.5%) experienced grade ≥2 irAEs, including 134 patients with grade 2 irAEs and 86 with grade ≥3 irAEs. Propensity score matching extracted 198 patients with and without grade ≥2 irAEs. The onset of grade ≥2 irAEs was associated with longer median progression‐free survival (PFS) (8.3 months vs. 4.5 months, p = 0.003) and overall survival (OS) (20.4 months vs. 14.3 months, p = 0.031) and a higher objective response rate (ORR) (44.8% vs. 30.2%, p = 0.004). Patients with grade 2 irAEs had significantly better oncological outcomes (PFS, OS, and ORR) than grade ≤1 and ≥3 irAEs. Patients with grade ≥3 irAEs had worse outcomes than grade 2 irAEs. Endocrine and skin irAEs were related with better survival outcomes, and the rate of severities was lower in these categories. In conclusion, the occurrence of irAEs, particularly low‐grade irAEs, was predictive of pembrolizumab efficacy in patients with platinum‐pretreated advanced UC. Abstract : Kaplan‐Meier plots analysis showing OS for 396 patients with grade ≥2 irAEs and with grade 1 or no irAEs who survived longer than 3 months after propensity score matching. The onset of grade ≥2 irAEs was associated with longer median OS (20.4 months vs. 14.3 months, p = 0.031).